Peningkatan Kemampuan Sosial Emosional Anak Kelompok B melalui Kegiatan Mendongeng di RA Hidayat Kota Probolinggo - Fitriatul Aini; Ferra Lorettha; Agustiarini Eka Dheasari (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
The pupose of this reseach to describe the application of story telling methods to improve social emotional in childern aged 5 to 6 years. As for the emotional social indikators studied, among others: 1) want to hear other people talk; 2) discipline to dbey the rules; 3) patiently waiting for their turn. Based on observation in group B RA Hidayat kec. Kanigaran there were findings of social emotional problems. This try pe of research is classroom action research, the tecniqius use in data collection are observation. As for the results of the prcycle study, the average grade value obatained by group B childern was only about 45,5 % . In cycle 2 it incresead againby 77 %. Then story telling methods can improve the socid emotional aspects of group B childern in RA Hidayat